A Comparison of the Responsiveness of the Postural Assessment Scale for Stroke and the Berg Balance Scale in Patients With Severe Balance Deficits After Stroke. Issue 4 (October 2020) - Huang, Yi-Jing; Lin, Gong-Hong; Lee, Shih-Chieh; Hsieh, Ching-Lin
Abstract : Background and Purpose: Previous evidence that the Postural Assessment Scale for Stroke (PASS) and the Berg Balance Scale (BBS) have similar responsiveness is doubtful. Compared with the BBS, the PASS has more items assessing basic balance abilities (such as postural transition during lying and sitting), so it should be more likely to detect changes in patients with severe balance deficits. We aimed to compare the responsiveness of the PASS and the BBS in patients with stroke who have severe balance deficits. Methods: The PASS and BBS scores of 49 patients with severe balance deficits at 14 and 30 days after stroke were retrieved. The group-level responsiveness was examined with the standardized response mean (SRM). The individual-level responsiveness was examined by the proportion of patients who achieved clinically significant improvements (ie, their pre-post change scores in the PASS/BBS exceeded the minimal detectable change with 95% confidence of each measure). The responsiveness of the 2 measures was compared using the bootstrap approach. Results and Discussion: The comparisons of responsiveness showed significant differences between the PASS and the BBS at both the group and individual levels. At the group level, the PASS indicated moderate changes in balance function (SRM = 0.79), but the BBS indicated only small changes (SRM = 0.39). At the individual level, the PASS showed that 42.9% of patients had clinically significant improvements, while the BBS showed that only 6.1% of patients had clinically significant improvements. Conclusions: Compared with the BBS, the PASS was better able to detect balance improvements in patients having severe balance deficits. The PASS is recommended as an outcome measure to detect change in balance in patients with stroke who have severe balance deficits.